A Holocene high-resolution record of aquatic productivity, seasonal anoxia and meromixis from varved sediments of Lake Łazduny, NE Poland: insight from a novel multi-proxy approach - Andrea Sanchini (PANGAEA, 2020)
Anthropogenic eutrophication and spreading anoxia in freshwater systems is a global concern. Little is known about anoxia in earlier historic times under weaker human impact, or under prehistoric natural conditions with different trophic, land cover and climatic regimes. We use a novel approach combining high-resolution hyperspectral imaging with μ-XRF and HPLC-pigment data, which allows us to assess chloropigments (productivity) and bacteriopheophytin (anoxia) at seasonal subvarve-scale resolution. Our ~ 9700 cal a BP varved sediment record from NE Poland suggests that productivity increased stepwise from oligotrophic Early Holocene conditions (until ~ 9200 cal a BP) to mesotrophic conditions in the Mid- and Late Holocene. Natural eutrophication was mainly a function of progressing landscape evolution with intense weathering under dense forest and warm-moist climatic conditions. Generally, anoxia increased with increasing productivity. Seasonal anoxia and some multi-decadal periods of meromixis were the common mixing patterns throughout the Holocene except for a period of persisting meromixis between ~ 5200 and 2000 cal a BP. Anthropogenic deforestation around 400 cal a BP resulted in substantially better lake oxygenation despite high productivity. In this small lake, aquatic productivity and lakeshore forest cover (wind shield) were more important factors controlling oxic/anoxic conditions than Holocene temperature variability.